Non-convex polyhedral volume of interest selection - Fuchs, Raphael; Welker, Volkmar; Hornegger, Joachim (Computerized Medical Imaging and Graphics, 2010)
We introduce a novel approach to specify and edit volumes of interest (VOI for short) interactively. Enhancing the capabilities of standard systems we provide tools to edit the VOI by defining a not necessarily convex polyhedral bounding object. We suggest to use low-level editing interactions for moving, inserting and deleting vertices, edges and faces of the polyhedron. The low-level operations can be used as building blocks for more complex higher order operations fitting the application demands. Flexible initialization allows the user to select within a few clicks convex VOI that in the classical clipping plane model need the specification of a large number of cutting planes. In our model it is similarly simple to select non-convex VOI. Boolean combinations allow to select non-connected VOI of arbitrary complexity. The polyhedral VOI selection technique enables the user to define VOI with complex boundary structure interactively, in an easy to comprehend and predictable manner. © 2009 Elsevier Ltd. All rights reserved.